Study of the lymphatics of the mammary gland with the golden radius 198 - Leborgne, Félix; Leborgne, Raúl; Schaffner, Eduardo; Leborgne (h), Félix E (Cirugía del Uruguay, 2020)
Presented at session 11th April 1956